The Effect of Tax Planning and Managerial Ownership on Firm Value in Property, Real Estate Sector Companies and Construction of registered buildings on the Indonesia Stock Exchange (IDX) - Resi Rosanti; Lilis Kartika; Maman Nurochman (LPPM Universitas Sebelas April, 2020)
Tax planning tends to fall in some companies shown to be ETR (Effective Tax Rate) higher because of the company's revenue burden greater than pre-tax revenue, which, if the tax burden rises then will be followed by an increase in ETR anyway. The low level of managerial ownership in this case indicates that there are still few management parties that have shares in the company. The company's value has fallen on some companies, which may be due to the fact that there is still a declining profit due to the rising tax burden. It also caused the stock price to fall so that the stock price was below its book value or its actual value. The research aims to determine the impact of tax planning and managerial ownership on the company value of the property, real estate and building construction sectors listed on the Indonesia Stock Exchange (IDX) both partially and simultaneously with the 2016-2019 research period. The research method used is quantitative. Data collection techniques with Purposive sampling, and the results of 9 companies sample. The research results show that significant tax planning of 0.072 > 0.05 then partially tax planning variables do not affect on company values, and significant managerial ownership of 0.000 < 0.05 then partially managerial ownership variables have a positive affect on company values. And the simultaneous tax planning and managerial ownership of 0.000 < 0.05 then had a positive and significant impact on the value of the company. The coefficients of determination obtained at 0.630 or 63%, while the remaining 37% was influenced by other factors not included in this research variabl.